2018
DOI: 10.1007/s10815-018-1187-4
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of two whole genome amplification techniques in frame of multifactor preimplantation genetic testing

Abstract: PurposeTo compare multiple displacement amplification and OmniPlex whole genome amplification technique performance during array comparative genome hybridization (aCGH), Sanger sequencing, SNaPshot and fragment size analysis downstream applications in frame of multifactor embryo preimplantation genetic testing.MethodsPreclinical workup included linked short tandem repeat (STR) marker selection and primer design for loci of interest. It was followed by a family haplotyping, after which an in vitro fertilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Title and abstract screening resulted in 73 papers. Full text screening resulted in 26 publications fulfilling the inclusion criteria . No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Title and abstract screening resulted in 73 papers. Full text screening resulted in 26 publications fulfilling the inclusion criteria . No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“… 38 For monogenic diseases, sequencing of PCR products was initially used to directly detect variants in biopsied embryo cells. 12 , 13 , 14 However, owing to the limitations of contamination and ADO, 15 , 16 in recent years, family‐based linkage analysis has become a standard method using STR or SNP haplotype analysis to indirectly determine the variants. 17 , 18 , 19 , 20 Handyside et al developed the Karyomapping method, which could be applied to any single‐gene defect within the regions covered by the SNP loci and overcame the difficulty of ADO at the single‐cell level.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 , 14 However, every WGA methods can result in false negative or positive single‐nucleotide variants (SNVs) owing to amplification preference of the primers and/or allele dropout (ADO), leading to misdiagnosis. 15 , 16 Family‐based linkage analysis has now become a popularized method by testing short tandem repeats (STRs) or SNPs to indirectly determine variants by haplotype, 17 , 18 , 19 , 20 , 21 , 22 and some of these researches have also confirmed that gene variants and chromosome aneuploidies can be detected simultaneously. 18 , 19 , 20 , 21 , 22 Massively parallel sequencing, like MARSALA, enables direct genotyping and haplotype analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, new technologies have also been applied in PGT for HLA typing, such as the use of whole genome amplification of the biopsied sample prior to STR testing. Furthermore, SNPs, instead of STRs, can be used to define the haplotypes across the genomic regions and such strategies are supported by the use of SNP arrays (for example the commercialized procedure known as karyomapping) or, more recently, NGS [44][45][46]. The latest technologies can assist in overcoming the limitations of the PCR-based linkage approach for HLA typing, such as the restriction in the number of STRs that can be co-amplified, the time required to characterize new STRs for a family (if the ones already available are not informative), and the need to optimize a new protocol for each couple.…”
Section: Overview Of Pgt-hla Methodologymentioning
confidence: 99%